Factor affecting students’ academic performance in UiTM Seremban 3 / Ezzatul’ain Muhamad and Nur Zahirah Md Suib - Muhamad, Ezzatul’ain; Md Suib, Nur Zahirah (2022)
Students’ academic performance is a key feature in education. This study was therefore conducted primarily to assess the factors affecting students’ academic performance in UiTM Seremban 3. The study concludes that self-motivation, family stress, distraction from friends, and distraction by social media have serious influence on students’ academic performance. Among the other elements examined in this research, the results show that both internal and external pressure on a student is a primary factor to the state of academic performance.